A study on demographic factors that influence the usage of Takaful products / Ahmad Safuan Rosly - Rosly, Ahmad Safuan (Faculty of Business and Management, 2010)
This study is conducted to identify what is the relationship between demographic factor and the usage of Takaful product. On this research, the employee of the private sector and government sector in Damansara height has been chosen as sample of the study in order to analyze on that topics. This study presents new empirical evidence on the relationship between demographic factor and the usage of Takaful product. Recently, Takaful industries are well growing and some of the Takaful provider has predicted that these industries will keep growing in the future. Some of factor that contributed to the usage of the Takaful product has been identified. Demographic factor such as age, gender, race, education level and income is the independent variable and usage of Takaful product is the dependent variable. Hence, this research is conducted to whether demographic factor have a positive relationship or negative relationship toward the usage of Takaful product.